1994
DOI: 10.1007/bf00188659
|View full text |Cite
|
Sign up to set email alerts
|

Semiempirical calculations of the oxygen equilibrium isotope effect on binding of oxamate to lactate dehydrogenase

Abstract: Semiempirical methods have been used in an attempt to predict theoretically the experimentally observed value of 0.9840 for the oxygen isotope effect on binding of oxamate to lactate dehydrogenase. The overall strategy involved vibrational analysis of oxamate in two different environments; that of the active site residues and in aqueous solution. The comparison of calculated values with the experimentally determined isotope effect proved the AM1 Hamiltonian to be superior to the PM3 Hamiltonian in this modelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…As binding usually involves weak, noncovalent interactions, these isotope effects were for many years neglected. Only a few studies have been aimed directly or indirectly , at kinetic isotope effects on binding. In the remaining part of this Review, we will discuss only equilibrium isotope effects on binding and we will be using the BIE symbol to denote them.…”
Section: Isotope Effectsmentioning
confidence: 99%
“…As binding usually involves weak, noncovalent interactions, these isotope effects were for many years neglected. Only a few studies have been aimed directly or indirectly , at kinetic isotope effects on binding. In the remaining part of this Review, we will discuss only equilibrium isotope effects on binding and we will be using the BIE symbol to denote them.…”
Section: Isotope Effectsmentioning
confidence: 99%
“…In the mid 90s, we studied the oxygen isotope effect of oxamate carboxylic oxygen atoms on its binding to lactic dehydrogenase both experimentally and theoretically . These studies showed that changes in the hydrogen bonding network between the aqueous solution and LDH enzyme active site can lead to significant binding isotope effects (BIEs).…”
Section: Introductionmentioning
confidence: 99%
“…In the mid 90s, we studied the oxygen isotope effect of oxamate carboxylic oxygen atoms on its binding to lactic dehydrogenase both experimentally 18 and theoretically. 19 These studies showed that changes in the hydrogen bonding network between the aqueous solution and LDH enzyme active site can lead to significant binding isotope effects (BIEs). With the above-mentioned applications of LDH in diagnostics, BIEs may prove to be very useful means of determinations of the conformation and type of different LDH isozymes.…”
Section: Introductionmentioning
confidence: 99%
“…where superscripts r and p refer to reactant and product isotopomers, respectively. Usually, equilibrium isotope effects are computed only approximately: 1,2,3,4,5,6,7,8,9,10,11,12,13 In particular, effects due to indistinguishability of particles and rotational and vibrational contributions to the EIE are treated separately. Furthermore, the vibrational motion is approximated by a simple harmonic oscillator and the rotational motion is approximated by a rigid rotor.…”
Section: Introductionmentioning
confidence: 99%